2011
DOI: 10.1074/mcp.m110.006908
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei Mitochondrial Respiratome: Composition and Organization in Procyclic Form

Abstract: The mitochondrial respiratory chain is comprised of four different protein complexes (I-IV), which are responsible for electron transport and generation of proton gradient in the mitochondrial intermembrane space. This proton gradient is then used by F o F 1 -ATP synthase (complex V) to produce ATP by oxidative phosphorylation. In this study, the respiratory complexes I, II, and III were affinity purified from Trypanosoma brucei procyclic form cells and their composition was determined by mass spectrometry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 57 publications
5
73
0
Order By: Relevance
“…Alternative pathways described in trypanosomes are similar to the alternative pathways described in other protists, green plants and fungi: an alternative oxidase (AOX or TAO), a type-II NADH dehydrogenase (NDA or TAD) (Acestor et al, 2011;Fang and Beattie, 2002) and a glyceraldehyde-3-phosphate dehydrogenase (G3PD), the activity of which compensates for the absence of oxidative phosphorylation during the bloodstream stage (Chaudhuri et al, 2006). Our analyses demonstrated that trypanosomal alternative oxidase and type-II NADH dehydrogenase are homologous to those of the other organisms.…”
Section: Alternative Pathwaysmentioning
confidence: 82%
See 4 more Smart Citations
“…Alternative pathways described in trypanosomes are similar to the alternative pathways described in other protists, green plants and fungi: an alternative oxidase (AOX or TAO), a type-II NADH dehydrogenase (NDA or TAD) (Acestor et al, 2011;Fang and Beattie, 2002) and a glyceraldehyde-3-phosphate dehydrogenase (G3PD), the activity of which compensates for the absence of oxidative phosphorylation during the bloodstream stage (Chaudhuri et al, 2006). Our analyses demonstrated that trypanosomal alternative oxidase and type-II NADH dehydrogenase are homologous to those of the other organisms.…”
Section: Alternative Pathwaysmentioning
confidence: 82%
“…Most of these 19 proteins were also identified in N. gruberi. Out of the 34 additional CI subunits described in T. brucei as potentially kinetoplastid-specific (Acestor et al, 2011;, we found 14 subunits in E. gracilis (NDTB1,2,5,6,11,12,17,18,22,25,28,29,31 and 34) ( Figure 2). Three of these subunits were also identified in D. papillatum (NDTB26/29/32) and 10 in N.…”
Section: Complex Imentioning
confidence: 92%
See 3 more Smart Citations